Comparative metabolomic profiling reveals molecular mechanisms underlying growth promotion and disease resistance in wheat conferred by Piriformospora indica in the field - Yuejiao Li; Meiying Bi; Shuqin Sun; Guangsheng Li; Qian Wang; Ming Ying; Liang Li; Xiurong Yang (Plant Signaling & Behavior, 2023)
Piriformospora indica, a plant root-colonizing basidiomycete fungus, exhibits strong growth-promoting activity in symbiosis with a broad range of plants. Here, we report the potential of P. indica to improve growth, yield, and disease resistance in wheat in the field. In the present study, P. indica successfully colonized wheat through chlamydospores and formed dense mycelial networks that covered roots. Plants subjected to the seed soaking (SS) treatment with P. indica chlamydospore suspensions enhanced tillering 2.28-fold compared to the non-inoculated wheat in the tillering stage. In addition, P. indica colonization promoted vegetative growth significantly during the three-leaf, tillering, and jointing stages. Moreover, the P. indica-SS-treatment enhanced wheat yield by 16.37 ± 1.63%, by increasing grains per ear and panicle weight and decreased damage to wheat shoot and root architecture markedly, with high field control effects against Fusarium pseudograminearum (81.59 ± 1.32%), Bipolaris sorokiniana (82.19 ± 1.59%), and Rhizoctonia cerealis (75.98 ± 1.36%). Most of the primary metabolites, such as amino acids, nucleotides, and lipids, involved in vegetative reproduction were increased in P. indica-SS-treatment plants, whereas secondary metabolites, such as terpenoids, polyketides, and alkaloids, decreased following P. indica inoculation. The up-regulated processes of protein, carbohydrate, and lipid metabolism indicated that P. indica colonization increased growth, yield, and disease resistance via the acceleration of plant primary metabolism. In conclusion, P. indica improved morphological, physiological, and metabolic substance levels, and further promoted its growth, yield, and disease resistance in wheat.